Methodological foundations of monitoring the extraction of sand-gravel mixture in flood-plains (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article discusses the methodological foundations of the organization of geoecological monitoring of the extraction of sand-gravel mixture (GHS) in floodplains and riverbeds of Kyrgyzstan. The relevance of the study is due to the increased anthropogenic impact causing channel deformations, coastal erosion and ecosystem degradation. A comprehensive observation technique based on a combination of remote sensing of the Earth, geographic information systems (GIS), field hydrological research and bioindication is proposed. The stages and principles of monitoring have been developed to ensure the objectivity and consistency of the assessment of the consequences of GHG mining. A set of indicators has been introduced, including morphometric, hydrochemical and biological parameters, which make it possible to predict changes and develop measures to reduce geoecological risks. The implementation of the proposed system of measures contributes to the formation of a regional GIS platform for monitoring and sustainable environmental management in the mountainous regions of Kyrgyzstan.
Keywords: sand and gravel mixture, monitoring, floodplain, river, bottom sediments, geoecological risk, GIS